Peran Pola Aliran Sungai dan Proses Geomorfologi dalam Penataan Lingkungan Kampung Jodipan - Zarrah Azzahrawani Banawi; Maulidiyah Nurizzah Intan Sari (Jurnal Pendidikan Geografi Undiksha, 2026)
This study explored the influence of river flow patterns and geomorphological processes on the environmental management of Jodipan Village. The transformationof this area began when the former slum along the Brantas River was revitalized into a community, based tourist destination that gained attention from both local and international visitors. A literature based approach was used to examine the physical, social, and economic changes that occurred during the development process, as well as the contributions of the government, local, community and private sector. The results show that the rectangular river flow pattern shaped by geological structures, along with the presence of alluvial and latosol soils, plays a significant and management strategies. The physical transformation not only enhances visual appeal and environmental quality, but also supports local economic growth and encourages positive behavioral changes among residents in maintaining cleanliness and environmental sustainability.